Anti-Bacterial Effectiveness Test of Tamarind Leaf Extract (Tamarindus indica) and Turmeric Extract (Curcuma longa) against Klebsiella Pneumonia Bacteria: Uji Efektivitas Anti Bakteri dari Ekstrak Daun Asam Jawa (Tamarindus indica) dan Ekstrak Kunyit (Curcuma longa) terhadap Bakteri Klebsiella Pneumonia - Juliana, Tiara; Rini, Chylen Setiyo (Universitas Muhammadiyah Sidoarjo, 2020)
Tamarind and turmeric are used by the community to treat respiratory diseases and fever obtained at the Pandaan market. This study aims to determine the effectiveness of tamarind leaves and turmeric by maceration in inhibiting Klebsiella pneumoniae bacteria at various concentrations. Antibacterial activity test using Kirby-Bauer disc diffusion method with concentrations of 25%, 50%, 75%, and 100%. Tamarind and turmeric leaves used maceration extraction method by immersion using 96% ethanol as solvent. The positive control used was Penicillin while the negative control used was DMSO 10%. The concentrations of the samples used were: tamarind leaf extract with concentrations of 25%, 50%, 75%, and 100%; turmeric extract concentrations of 25%, 50%, 75%, and 100%; a combination of 25% tamarind leaf extract and 75% turmeric extract; a combination of 50% tamarind leaf extract and 50% turmeric extract; combination of 75% tamarind leaf extract and 25% turmeric extract. The total number of samples is 33 samples. The best inhibition was obtained from the results of the inhibition zone > 20 mm. Turmeric extract had the best antibacterial activity against the growth of Klebsiella pneumoniae bacteria at concentrations of 50%, 75%, and 100%. With each inhibition zone diameter of 21.5 mm; 29.83 mm ; and 33.16 mm. Based on the results of the Two Way ANOVA test with a 95% confidence level (p > 0.05), it was found that there was no significant effect between samples of tamarind leaf extract and turmeric extract on the growth of Klebsiella pneumoniae bacteria.